On the move to meaningful Internet Systems: OTM 2013 Conferences : Confederated International Conferences: CoopIS, DOA-Trusted Cloud, and ODBASE 2013, Graz, Austria, September 9-13, 2013. Proceedings - Panetto, Herve; Dillon, Tharam; Eder, Johann; Bellahsene, Zohra; Ritter, Norbert; Leenheer, Pieter; Dou, Deijing; Meersman, Robert (Lecture Notes in Computer Science, 2013)
This volume constitutes the refereed proceedings of the confederated international conferences: Cooperative Information Systems (CoopIS 2013), Distributed Objects and Applications (DOA-Trusted Cloud 2013), and Ontologies, Data Bases and Applications of SEmantics (ODBASE 2013) held as part of OTM 2013 in September 2013 in Graz, Austria. The 47 revised full papers presented together with 6 short papers and 5 keynotes were carefully reviewed and selected from a total of 137 submissions. The papers are organized in topical sections on business process management; process modelling; service management; social networking; models and schemas; technical advances in cloud computing; towards trusted cloud computing; privacy for the cloud; querying and mining semantic information; semantic matching and mapping; semantic information management; semantics in use.